1999
DOI: 10.1034/j.1399-6576.1999.430915.x
|View full text |Cite
|
Sign up to set email alerts
|

A non‐thoracic operation for a patient with single lung transplantation

Abstract: The number of lung transplants performed annually is increasing. It is becoming more likely that these patients will present post transplantation to anesthesiologists who have little experience in dealing with the physiological, pharmacological, medical and surgical problems that these patients present. This article discusses the management of a patient presenting for surgery after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This, of course, places the recipient at risk for both aspiration and infection. In the normal lung, autonomic innervation is responsible for regulating airway tone, however, there seems to be no clinically significant change in bronchomotor tone after transplantation nor is there an increase in the incidence of airway hyperreactivity [46]. Bronchodilators continue to be effective although some investigations suggest their effect is slightly decreased.…”
Section: Anesthesia For Patients After Lung Transplantmentioning
confidence: 99%
“…This, of course, places the recipient at risk for both aspiration and infection. In the normal lung, autonomic innervation is responsible for regulating airway tone, however, there seems to be no clinically significant change in bronchomotor tone after transplantation nor is there an increase in the incidence of airway hyperreactivity [46]. Bronchodilators continue to be effective although some investigations suggest their effect is slightly decreased.…”
Section: Anesthesia For Patients After Lung Transplantmentioning
confidence: 99%
“…The drugs can also be administered via a nasogastric tube, if the use of suction can be avoided ( 73). It is suggested that the transplantation unit should recommend doses and routes of administration ( 118). Cyclosporine dose conversion for parenteral use may be difficult because of the individually variable intestinal absorption, and the parenteral solution is incompatible with many plastic materials ( 80).…”
Section: Anaesthesia For General Surgerymentioning
confidence: 99%
“…High oxygen content may also aggravate pulmonary manifestations in Goodpasture’s syndrome ( 34). Bronchoconstriction is possible in transplanted lungs, may be related to rejection, and may not respond to normal bronchodilator therapy ( 118).…”
Section: Anaesthesia For General Surgerymentioning
confidence: 99%
See 2 more Smart Citations